Synthesis of Cerium-Oxide Coated Platinum Core-Shell Structure Catalysts with Enhanced Stability and Activity via Atomic Layer Deposition. (16th August 2016) - Cao, Kun; Shi, Lu; Cai, Jiaming; Shan, Bin; Chen, Rong
Abstract : Cerium oxide has been deposited on the platinum nanoparticles' to form core shell structures which enhance the metal nanoparticles thermal stability as well as catalytic activity. It is found that growth rate of cerium oxide on Pt surface is faster than on alumina oxide support and form abundant Pt/cerium oxide interfaces. The catalytic performance of Pt/cerium oxide catalysts towards CO oxidation has been investigated in a micro flow reactor. The cerium oxide decorated Pt nanoparticles has demonstrated lower conversion temperature than bare Pt nanoparticles. Moreover the coated Pt nanoparticles show good sintering resistance up to 700 °C under atmosphere condition.